(3GdEQTGO aj eYQaI QLGd GdHNGQis - (3CHh fUQ CMeO Hf eMeO Hf GdMSjf Hf GdMSf Hf Ydj Hf QSJe GdHNGQj GdcdGHGPj,J (B398 (3g` s
(3ChdgG (B:s
(3MOKfG Gdabjg GdbGVi CHh GdhdjO gTGe CHf CMeO Hf gTGe Hf NGdO GdcfOi QVi Gddg Yfg s
(3BNQgG (B:s
(3bGd GdHNGQi eGJ SfI KfJjf hYTQjf heGJjf s
(3PcQ ajg ef CNQL GdHNGQi MOjKge ai GdLGeY GdUMjMs
(3hGMJL Hge ajg hUM MOjKge YfOg ef GdUMGHI hGdJGHYjfs
(3hPcQ TjhNg GdPjf bQC Ydjge hQhi Yfges
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B210 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B95s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B280 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B11 s
Keywords: (3GdJGQjNs